Document of decadent society of the 19th century: The context is Ekei Ki Bale Savyata and Babaji/ উনিশ শতকের অবক্ষয়িত সমাজের দলিল : প্রসঙ্গ একেই কি বলে সভ্যতা ও বাবাজী (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
From the second half of the 19th century, the dramas written in Indian languages ​​were mainly social-centered and focused on the multifaceted problems of society. Ranging from the various faults and anomalies of social customs, child marriage and the slippage of the upper castes, as the playwrights have eloquently depicted, the trend of drunkenness among the English-educated youth of the time has landed as an important social problem. This problem is mainly seen in early plays or farces. For example, Madhusudan Dutt's 'Ekei ke bale sabhyta' in Bengali, Assamese Hem Barua's 'Kaniar Kirtan' in Assamese, Madgaonkar's 'Bhojanbandhu Pantangwakhu' in Marathi, 'Babaji' in Oriya, etc. plays and farces can be specially mentioned. The immediate purpose of this essay is to shed light on how decadent and depraved the new English-educated Babu society and in society the drinking habit of zamindar class have become in the plays 'Ekei Ki Bale Sabhyta' (1860) by Madhusudan Dutta and 'Babaji' (1877) by Jagmohan Lala. In this comparative thought, not only the similarity but also the contrast is the history of the ups and downs of the society.
Keywords: 19th century; social customs; child marriage; English-educated youth; comparative thought